1995
DOI: 10.1103/physrevb.51.9026
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of the upper critical field of V/Ag and Nb/Cu superlattices

Abstract: The Takahashi-Tachiki equations, describing the critical properties of proximity-effect systems in the dirty limit, are solved exactly using the full eigenfunction expansion. Both parallel and perpendicular critical fields are calculated. The theory is applied to experimental data of Kanoda et aI. for V/Ag and of Chun et aI. for Nb/Cu, using the T, of the superconducting material and the diffusion coefficients of both materials as fit parameters. For the three-dimensional (3D) systems the fits compare nicely w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
2

Year Published

1996
1996
2005
2005

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 23 publications
5
23
2
Order By: Relevance
“…[2][3][4][5][6][7] For the first solution, the fitted parameters are close to what one knows from the measurements. However, the dimensional crossover, typical for S/N multilayers, appeared to lie at a much higher temperature than the measured one.…”
Section: Introductionmentioning
confidence: 60%
“…[2][3][4][5][6][7] For the first solution, the fitted parameters are close to what one knows from the measurements. However, the dimensional crossover, typical for S/N multilayers, appeared to lie at a much higher temperature than the measured one.…”
Section: Introductionmentioning
confidence: 60%
“…These are the systems for which a dimensional crossover is observed in the parallel upper critical field, that is, of which the layers have intermediate thicknesses. 9 The earlier Ref. 10 presented results according to the second solution, which is characterized by a ratio N S D S /N N D N well below one.…”
Section: ͑18͒mentioning
confidence: 99%
“…It was concluded that no thorough comparison of theory and experiment existed that considers absolute magnitudes of both parallel and perpendicular upper critical fields in multilayers of various layer thicknesses. We made an attempt 9,10 to such a comparison for two related systems: V/Ag and Nb/Cu. The exact solutions were calculated of the well-known TakahashiTachiki equations, 11 which constitute the most advanced proximity-effect theory currently available.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the best studied S/normal metal (N) proximity coupled multilayer [16,17] and, even very recently, many papers have been devoted to studying fundamental physical properties of this system [14,15,18,19]. The samples have been prepared by using two different deposition techniques, sputtering and molecular beam epitaxy (MBE).…”
Section: Introductionmentioning
confidence: 99%